Kajian taburan diabetis melalui projek pencegahan diabetis dalam komuniti (PDDK) di Selising, Pasir Puteh, Kelantan 1998 - Yasin K. J,; Liza Sharmini A.,; Mahiran A, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1999)
An intervention project for the prevention of Diabetes in the community (P.D.D.K)was implemented in the operational area of Selising Health Centre for 11 months.The objective of this cross sectional study with the help of community leaders is to determine the distribution and the prevalence of Diabetes Mellitus in this region.The study involved 1,114 cases. Samples were chosen by doing a random blood sugar test (RBS) and if the reading exceeded 8.0 mmol/L, cases would undergo fasting blood sugar (FBS). The test confirmed any aindividuals FBS is 11.0 mmol/L or more hence selected as study samples. The study results revealed that prevalence diabetesin this area was 5.03% with male to female ratio 1:1.24. The average age for new cases of diabetes was 52.5 years (ranging from 35 – 76 years). A total at 71.4% cases were from the high risk group (having a positive family history of diabetes, body mass index of more than 25 and smoked cigarette). Study on these new cases showed that 47% cases have body mass index of more than 25, 34% of cases smoked and 27% had a positive family history of diabetes. Age had a significant relation with body weight, RBS, smoking habit and hereditory (p<05).Health talks and dialogs organised during this project had successfully increased the understanding of the public about diabetes.